STUDENTS’ EXPERIENCES IN PROJECT-BASED SASAK DIGITAL STORYTELLING - Kahfi Amiruddin Umar; Marham Jupri Hadi; M. Mizanul Haq (ELITERATE : Journal of English Linguistics and Literature Studies, 2026)
Project-based digital storytelling can connect English use with learners’ cultural knowledge, yet relatively few qualitative studies have examined how secondary-school learners experience the process of representing local heritage through English rather than only reporting learning outcomes. This interpretive case study explored three Grade XI students’ experiences of creating English-language digital stories about Nyongkolan, Peresean, and Putri Mandalika in East Lombok, Indonesia. The approximately one-month project combined cultural inquiry, script development, digital production, and reflection. Semi-structured interviews constituted the primary evidence, while classroom observations, reflective journals, and completed digital stories provided contextual information. Data were interpreted using reflexive thematic analysis. Participants described the project as encouraging inquiry beyond classroom materials, particularly through family, community, direct-observation, and online sources. They also reported opportunities to expand culture-related vocabulary, practice narrative writing and spoken narration, and communicate culturally specific meanings in English. Evidence of deeper cultural interpretation was strongest in the Nyongkolan and Peresean accounts, while the available Putri Mandalika evidence more clearly reflected engagement than a comparable change in cultural understanding. The study therefore presents culture-based digital storytelling as a promising, context-sensitive project design for EFL learning, while not claiming measured gains in proficiency or intercultural competence.